Legal Consequences for Wrong Land Plot Objects in the PTSL Program (Case Study in Lemahkarya Village) - Amaliya, Lia; Amaey , Amaey; Oktapianti, Desi Ayu; Wiranata, M. Ardi; Siregar, Piki Hendiko; Ramadani, Trisna; Jaya, Yudha Yolandha (Jurnal Hukum dan Keadilan, 2024)
This research examines errors in land parcels in certificates that have been issued in the Complete Systematic Lan Registration Program (PTSL), errors in land parcels in certificates that have been issued result in legal defects or administrative defects. By using research question: Legal consequences of Wrong Land Plot Objects in the PTSL Program. The research method used is empirical. The results of the research show that “Article 62 paragraph (1) of the Regulation of the Head of the National Land Agency Number 3 of 2011 explains that certificates of land right which contain administrative legal defect can be canceled or changed by the government in recording the maintenance of land registration data according to statutory regulations.” The BPN and TUN systems allow for the cancellation of certificates, which may then be reissued or re-registered